Straits settlements order, rules and reulations 1889-1940 [1937-1939] (Petaling Jaya : Arkib Negara)
Mengandungi perkara-perkara berkaitan Air Navigation (Colonies, Protectorates and Mandated Territories) order 1927; Aliens Ord. (Cap. 90); Foreshores Ord. (Cap. 122); Military Manoeurres Ord. (Cap. 103); Children and young persons (places of Detention) ordinance, 1937 (no. 46 of 1937); currency Ord. (No. 23/38); Local Forces (increased expenditure) ordinance, 1938 (no. 2 of 1938).